Synthesis of artemisinin derived glycoconjugates inspired by click chemistry - Goswami, Lakshmi; Paul, Sayantan; Kotammagari, Tharun K.; Bhattacharya, Asish K. (New Journal of Chemistry, 2019)
Herein we describe the synthesis of artemisinin based glycoconjugates (9a-i) through employing a Cu(i)-catalysed reaction between -propargylated dihydroartemisinin (7a) and azido sugars (8a-i), with moderate to excellent yields. Our synthesized artemisinin based glycoconjugates (9a-i) could prove to be an interesting class of bioactive molecules, suitable for the study of their various biological activities.

Synthesis of artemisinic acid derived glycoconjugates and their anticancer studies - Kotammagari, Tharun K.; Paul, Sayantan; Barik, Ganesh K.; Santra, Manas K.; Bhattacharya, Asish K. (Organic & Biomolecular Chemistry, 2020)
Glycoconjugates, due to their diverse functions, are widely regarded as biologically important molecules. Artemisinic acid 1 occurs naturally in the plant Artemisia annua and is considered to be the biogenetic precursor of the antimalarial drug, artemisinin 2. We report herein the design and synthesis of diverse artemisinic acid derived glycoconjugates. We have synthesized 12-O-artemisinic acid-glycoconjugates (7a-k) and 12-N-artemisinic acid-glycoconjugates (8a-k) by utilizing Cu(i)-catalyzed azide-alkyne cycloaddition reactions (Click chemistry) with various synthesized sugar azides (6a-k) in good to excellent yields along with two fluorescently labeled compounds, 12-O-artemisinic acid-glycoconjugate 11 and 12-N-artemisinic acid-glycoconjugate 12, to investigate the mode of action of these compounds in biological systems. All the synthesized artemisinic acid glycoconjugates were assayed for their efficacy against the MCF7 cell line. Our anticancer studies indicated that all the synthesized compounds inhibited the growth of MCF7 cells in a dose dependent manner, barring compounds 4 and 7d. However, these compounds exhibit moderate cytotoxicity, as is evident from their IC50 values.

Short review on the synthetic routes for the antiepileptic drug (S)-levetiracetam - Paul, Sayantan; Bhattacharya, Asish K. (Organic Process Research and Development, 2024)
Epilepsy is a chronic disorder characterized by recurrent unpredictable seizures. Levetiracetam (Keppra) was introduced by UCB for the treatment of partial onset seizures in patients above 16 years of age diagnosed with epilepsy. This review reports synthetic strategies available for the synthesis of (S)-levetiracetam and will certainly aid the quest for the development of new routes for its synthesis.
Keywords: antiepileptic drug; butyrolactam; epilepsy; levetiracetam; synthesis

Strategies employing transition-metal free conditions for C-C bond formation in indoles - Ghodake, Balaji M.; Paul, Sayantan; Bhattacharya, Asish K. (ChemistrySelect, 2024)
Indole motifs are omnipresent in nature and can be found in many natural products as well as pharmaceuticals. It is for this reason synthetic transformations of indole have become a topic of interest for the organic and medicinal chemist community for decades. In this review, we have emphasized the functionalization of indoles via transition-metal-free approaches. This review touches on many aspects in different sub-sections, which gives a proposition of the tactics employed for the functionalization of indoles and an overview of the road ahead. In this review, essentially transition-metal-free conditions for C-C bond formation reactions in indoles has been explored. This review describes various approaches of functionalization at the C-2, C-3, C-4 and C-7 position of indoles which comprises arylation, alkenylation, acylation, formylation, alkylation, bisindolyl and cyclization strategies. Also, strategies incorporating N-alkylation/arylation has also been covered. image
Keywords: Alkylation; Arylation; formylation; Indole; transition-metal free